The touristic photographic representation of Andean identity in the Marca Peru’s Instagram - Gonzales-Parra, Sharon (2024)
This study analyzes the representation of Andean identity in three travel photographs shared about Cusco by Brand Peru on Instagram from 2023. Its approach is qualitative with an ethnographic design. Nineteen semi-structured interviews were conducted to learn about and interpret the perceptions of university students of Tourism and Anthropology at the Universidad Nacional San Antonio de Abad (Cusco). The results show that the photographs do not represent the Andean identity because they do not include the diversity of elements that make it up. Instead, the images tend to disseminate mercantilist, stereotyped and superficial discourses about the city of Cusco and its Andean characteristics. Due to the scarce information in this context, it is recommended to continue with research along the lines of the analysis of the representation of Andean identity in photographs on various social media platforms.